Effect of bacterial inoculation on co-composting of lavender (Lavandula angustifolia Mill.) waste and cattle manure - Greff, Babett (3 Biotech, 2021)
The primary purpose of this study was to investigate the influence of Cellulomonas flavigena and Streptomyces viridosporus, as a bacterial inoculant, on the compostability of post-extraction lavender waste. The major physicochemical, microbiological, and biological properties of the composting materials were monitored for 161 days. The technology developed was shown to improve the compostability of recalcitrant herbal residues. The use of lavender waste beneficially affected the composting process by extending the thermophilic phase, accelerating the degradation of organic matter, and elevating the viable counts of useful microorganisms; however, adverse effects were also observed, including an increased carbon-to-nitrogen ratio (19.05) and a decreased germination index (93.4%). Bacterial inoculation was found to preserve the nitrogen content (2.50%) and improve the efficiency of biodegradation. The Salmonella- and Escherichia coli-free final composting products were mature, stable, and ready for soil application. To the authors’ knowledge, no previous research has investigated the compostability of lavender waste. Likewise, this is the first study that has used strains of C. flavigena and S. viridosporus in combination to facilitate a composting process.